(untitled) (Research, Society and Development, 2021)
This study evaluated the mechanical strength correlated to the percentage of the total volume of weld and porosities of Co-Cr alloy joints welded with TIG technique. Thirty specimens were perpendicularly sectioned to the long-axis and rejoined by using X30-shaped joint design with TIG welding. They were divided into 3 groups (n=10): the CG1 with a 60-A depth and 90-ms pulse; the CG2 with a 60-A depth and 120-ms pulse and the CG3 with a 60-A depth and 160-ms pulse. The specimens were submitted to nondestructive tests: radiographic inspection, penetrant liquid and Micro- CT (to calculate the percentage of the total volume of welding and the porosities) and then tested with 3-point bending. The fracture surfaces were analyzed with scanning electron microscopy (SEM). The data were statistically analyzed with 1-way ANOVA and the Tukey post hoc test for all the variables which were analyzed: flexural strength, total volume of weld and porosities. Pearson correlation test was also applied (ɑ=.05). The 1-way ANOVA showed that the factors machine parameters were not significant for flexural strength values (P=.231), the total volume of weld (P=.057) and porosities (P=.057). There are no significant relationships between any pair of variables after Pearson correlation test (P >.050). This, suggesting that the three machine regulation can be an option for joining prefabricated Co-Cr rods in this kind of union.